Evaluating the correlation between the lateral pterygoid muscle attachment type and internal derangement of the temporomandibular joint with an emphasis on MR imaging findings - DERGİN, GÜHAN; GARİP, HASAN; GÖZNELİ, RİFAT (CHURCHILL LIVINGSTONE, 2012)
Objectives: Disc displacement is accepted as one of major findings in temporomandibular disorders. Correlation between lateral pterygoid muscle (LPM) attachment type to the disc condyle complex and TMJ dysfunction has rarely been discussed and still not clarified. The purpose of this study was to assess the prevalence LPM attachment type to the disc condyle complex, and to investigate whether these attachment types are linked to MR imaging findings of ID and TMJ dysfunction in a Turkish population. Study design: Ninety-eight TMJs in 49 patients (32 males, 17 females, mean age = 36 years) with one of either: TMJ clicking, TMJ locking, restricted movement of the jaw, or pain in the TMJ region, were included. According to the clinical findings and data obtained from MRI examinations, TMJs dysfunctions were classified. LPM attachments to the condyle disc complex were categorized into three different types. Correlation between TMJ dysfunction and LPM attachments to the condyle disc complex was evaluated. Results: Of 98 TMJs in 49 patients (32 males, 17 females, mean age = 36 years), 47 TMJ's (%48) were evaluated as normal, 35 (%35.7) had a disc displacement with reduction and 16 (%16.3) TMJ had a disc displacement without reduction. Arthritis was seen in 49 TMJ's (%50). LPM attachments to the condyle disc complex were as follows: Type 1(29.6%), Type II (40.8%), and Type III (29.6%). There was no statistically significant difference between the type of muscle attachment and the presence or absence of disc displacement (p = 0.481), disc degeneration (p = 0.752), articular surface degeneration (p = 0.117). Conclusions: There was no statistically significant correlation between the LPM attachment types and TMJ abnormalities. (c) 2011 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: TMJ; Lateral pterygoid muscle; Internal derangement; Muscle attachment; SUPERIOR HEAD; DISPLACEMENT; INSERTIONS; CONDYLE; FORCE; DISC; TMJ